(untitled) - Shepard, Alicia C. (Hoboken, N.J., 2007)
Bob Woodward and Carl Bernstein will always be famous for their part in untangling the Watergate scandal. Shepard, though, is far more interested in what happened afterward, and in examining the uneasy rewards of early success. Her prose can be clichéd, but her biographical curiosity is large; she seems to have interviewed almost everyone with a connection to her subjects. Other journalists played important roles in ending the Nixon Presidency, Shepard notes, but it was the film version of "All the President's Men," a retelling that left several colleagues feeling slighted, that enshrined "Woodstein" in "fame and glory." When the pair sold their papers to the University of Texas, for about five million dollars, one observer noted that they had become "as much a part of the story of Watergate and historical record as any of the people they reported on.
Keywords: Journalists,Watergate Affair, 1972-1974,Nhà báo; Press coverage; United States,Hoa Kỳ